Highly energetic nitramines: A novel platonizing agent for double-base propellants with superior combustion characteristics. (1st September 2018) - Elghafour, Ashraf M.A.; Radwan, Mostafa A.; Mostafa, Hosam E.; Fahd, Ahmed; Elbasuney, Sherif
Abstract: The burning rate-pressure relation of solid propellant is an exponential relation; this is means catastrophic combustion process in case of sudden increase in operating pressure. This study reports on novel approach to minimize the dependence of burning rate on combustion pressure using highly energetic nitramines (RDX). Nitramine-based double base propellants with RDX content up to 20 wt% were manufactured by solventless extrusion technology. The impact of RDX content on burning rate, specific impulse, exhaust velocity, and thrust were evaluated using small-scale ballistic evaluation rocket motor. Specific impulse (Is) was enhanced by 20%. The action burning time (tb ) was increased by 14%. The total thrust impulse (IFT) was significantly improved by 22%. One of the main outcomes of this study is that burning rate pressure exponent (n) was decreased significantly from 0.35 to 0.05. This novel ballistic performance finding means minimal change in burning rate with pressure variation. These findings confirmed that RDX has a dual function as energetic filler and platonizing agent. RDX blowing effect could alter the combustion mechanism by pushing the luminous flame from the burning surface. Furthermore, RDX decomposition can strengthen the platonization action. This is the first time ever to report on burning rate platonization using RDX. It can be concluded that many advantages have been achieved with one shot.